Фауна сипункулид (Sipunculoidea) Перуанско-Чилийского желоба - Мурина, В.В. (Вестник зоологии, 1973)
The material (41 specimens from 15 stations) was collected ih the south part of the Pacific Ocean during the expedition of the r/s "Kurchatov" in 1970. Eleven species of 3 genera were determined to be new for the deep-sea bottom fauna at the west coast of South America.